2017
DOI: 10.1007/s11695-017-2717-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aerobic or Aerobic-Strength Exercise on Body Composition and Functional Capacity in Patients with BMI ≥35 after Bariatric Surgery: a Randomized Control Trial

Abstract: The data suggests a positive effect of exercise on weight and PBF decrease after surgery, and it leads to significant improvement on aerobic capacity. Moreover, doing resisted exercise caused greater preserving of lean mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
0
30

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(189 citation statements)
references
References 67 publications
3
156
0
30
Order By: Relevance
“…We also observed a statistically significant change in the mean (±SD) 30‐second sit‐to‐stand test of 4 (±4) counts, which is approximately 2‐fold greater than changes reported in recent studies following bariatric surgery plus exercise intervention . Improvements in leg strength and endurance were inversely associated with BMI (positively associated with weight loss) age and diabetes.…”
Section: Discussionsupporting
confidence: 60%
“…We also observed a statistically significant change in the mean (±SD) 30‐second sit‐to‐stand test of 4 (±4) counts, which is approximately 2‐fold greater than changes reported in recent studies following bariatric surgery plus exercise intervention . Improvements in leg strength and endurance were inversely associated with BMI (positively associated with weight loss) age and diabetes.…”
Section: Discussionsupporting
confidence: 60%
“…For example, the three‐arm trial by Hassannejad et al reported in the abstract that both intervention arms were better than control for the primary endpoint of weight loss; however, they did not report the comparison between intervention arms, possibly because this comparison was not statistically significant. The only mention in the abstract of a between‐intervention comparison was for the secondary endpoint, which was statistically significant …”
Section: Resultsmentioning
confidence: 99%
“…En el paciente bariátrico, el objetivo de la evaluación es determinar la capacidad cardiorrespiratoria a través de una prueba de estrés cardiopulmonar que nos permita prescribir el ejercicio aeróbico y evaluar la respuesta al entrenamiento, teniendo en consideración sus experiencias previas habitualmente negativas relacionadas con el ejercicio y/o actividad física 8 . En la literatura revisada en la Tabla 2 6,[9][10][11][12][13][14][15][16][17][18] , la metodología más utilizadas es la evaluación directa del consumo máximo (VO 2max ) o pico de oxígeno mediante ergoespirometría, utilizando protocolos escalonados con duración de 5-12 min. Dentro de las evaluaciones indirectas la realización del protocolo de Astrand o Bruce puede entregar una estimación del VO 2max 19 y parámetros de carga interna y/o externa para la prescripción del ejercicio.…”
Section: Evaluación De La Capacidad Cardiorrespiratoriaunclassified
“…En la literatura seleccionada, para la evaluación funcional de tren inferior se utilizaron adaptaciones de la prueba de pararse y sentarse 6,17 y en tren superior se realizó la prueba de dinamometría de mano para determinar la fuerza de prensión 6 .…”
Section: Evaluación De La Fuerza Muscularunclassified
See 1 more Smart Citation